Adherence and Cost–Utility Analysis of Antiretroviral Treatment in People Living with HIV in a Specialized Clinic in Mexico City - Ivo Heyerdahl-Viau; Francisco Javier Prado-Galbarro; Santiago Ávila-Ríos; Osmar Adrian Rosas-Becerril; Raúl Adrián Cruz-Flores; Carlos Sánchez-Piedra; Juan Manuel Martínez-Núñez (Pharmacy)
This study aimed to evaluate the therapeutic adherence to antiretroviral therapy (ART) and the cost of care for people living with HIV (PLwHIV) in the Condesa Specialized Clinics (CSCs). A cross-sectional observational study was conducted using the Adherence Follow-Up Questionnaire developed by The AIDS Clinical Trials Group (ACTG) to measure adherence in 261 PLwHIV. An economic Markov model was developed to simulate clinical outcomes, health costs, and quality-adjusted life years (QALYs) over a 5-year horizon from the CSC perspective. The mean adherence index was 89.97, and 59% of the surveyed PLwHIV were non-adherent, but more than 95% of the population had an undetectable viral load, suggesting that ART remains effective in achieving clinical goals, even under suboptimal adherence conditions. More than half of the surveyed PLwHIV (60.54%) stated that they had stopped taking their ART at some point, and the three most frequent causes were forgetting (49.37%), being away from home (45.57%), and having a change in their daily routine (25.95%). The economic model showed a cumulative cost per PLwHIV of USD 8432 and 3.80 QALYs (USD 2218/QALYs), which is below the threshold of willingness to pay in Mexico (USD 13,790/QALY). These findings provide valuable information to guide public health decisions and resource allocation in HIV management in Mexico.